Interactive Power Point Implementation as a Digital Learning Media in Increase Understanding Theory Temperature and heat in students Elementary School - Fitrilia Widiyanti; Asep Bayu Dani Nandiyanto (International Journal of Research and Applied Technology (INJURATECH), 2021)
This study aims to analyze the application of interactive power point as a digital learning medium in increasing the understanding of temperature and heat theory in elementary school students. The study was conducted on 37 elementary school students in the city of Bandung using conventional teaching methods and demonstrations. We also use interactive power point media and Google Meet in the learning process. To determine the level of students' understanding of the material, researchers used evaluation techniques in the form of pre-test and post-test, each of which included as many as 20 questions through Google Form. The results showed that students got an average increase of 2.48 in learning outcomes. The increase shows that 68.92% of the material can be understood by students. This is because the learning process using conventional teaching methods, demonstrations, and interactive power point learning media can increase students' attention and focus, so they don't get bored while learning. Therefore, this study provides information that interactive power point media can be used as an interesting learning medium that can increase students' understanding of temperature and heat material.